Pengaruh Pembelajaran Contextual Teaching Learning (CTL) terhadap Kemampuan Koneksi Matematis Siswa SMP Ditinjau dari Gender - Cut Musriliani; Marwan Marwan; Bansu Irianto Ansari (Didaktik Matematika, 2015)
Contextual Teaching Learning (CTL) is a learning approach that can help teachers relate learning materials with students real-world situations and encourage them to make connections between their knowledge by the application in their life as members of the family and society. Mathematical connection ability includes finding the relationships between mathematics and its topics, mathematics and other subjects, and mathematics and daily life or the real world. The purposes of this study were (1) to know the difference in students mathematical connection ability before and after using CTL, (2) to know the difference in mathematical connection ability between male and female students, and (3) to know the effect of CTL on mathematical connection ability of VIII grade students of Junior High School in terms of gender. This study adopted a factorial design, a modified version of true experimental design. The subjects of the study were 34 students of class VIII-4 of SMP Negeri 3 Banda Aceh as experimental class without control class. The instrument of data collection was mathematical connection test. Data were analyzed using Analysis of Variance (ANOVA). The finding of the study shows that (1) there was a difference in students mathematical connection ability before and after using CTL, (2) there was no difference in mathematical connection ability between male and female students, and (3) there was a learning effect of CTL on mathematical connection ability of VIII grade students of Junior High School in terms of gender. The implications of this study demonstrate that learning mathematics with CTL approach was one of the efforts of teachers in teaching and learning activities in particular mathematics courses to improve male and female students' connection ability.